Laser cladding coating with in-situ synthesis TiC and Y-Ti-O composite reinforcement phase and preparation method of laser cladding coating

The in-situ self-generated TiC and Y-Ti-O composite reinforced phase coating prepared by laser cladding technology solves the corrosion problem of austenitic steel in liquid lead-bismuth eutectic alloy, achieving high hardness, high bonding strength and wear resistance, improving the corrosion resistance of the coating and extending the service life of the reactor.

CN121451183APending Publication Date: 2026-02-03JIANGSU JICUI SURFACE ENGINEERING TECHNOLOGY RESEARCH INSTITUTE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511853197.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-10
Publication Date
2026-02-03

AI Technical Summary

Technical Problem

Existing austenitic steels are not resistant to corrosion from liquid lead-bismuth eutectic alloys. The hard phase TiC is prone to segregation and has weak bonding with the matrix. The physical dispersion effect of rare earth oxide Y2O3 is limited, making it difficult to optimize the microstructure and properties of the coating.

Method used

A coating with in-situ self-generated TiC and Y-Ti-O composite reinforcing phases was prepared by laser cladding technology. Y2O3 reacts with Ti to generate Y2Ti2O7 and Y2TiO5 phases, which refines TiC grains and improves their distribution, forming Fe2AlCr alloy matrix phase, thus optimizing the coating microstructure and properties.

Benefits of technology

In a high-temperature liquid lead-bismuth environment, the coating exhibits high hardness, high bonding strength, good wear resistance, and excellent corrosion resistance, significantly improving the safety and service life of reactor structural materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121451183A_ABST
    Figure CN121451183A_ABST
Patent Text Reader

Abstract

The invention discloses a laser cladding coating with an in-situ synthesis TiC and Y-Ti-O composite reinforcement phase and a preparation method of the laser cladding coating, and belongs to the technical field of alloy protective coatings. The coating is cladded on the surface of the steel substrate; the coating comprises a Fe2AlCr alloy matrix phase and an in-situ synthesis reinforced phase which is dispersed and distributed in the Fe2AlCr alloy matrix phase, the in-situ synthesis reinforced phase comprises a TiC phase and a Y-Ti-O composite phase existing in the TiC phase. According to the invention, TiC is obviously refined and spheroidized by a unique composite structure containing phases in phases, and the distribution of TiC is improved, so that the hardness, the wear resistance, the bonding strength with a matrix and the high-temperature liquid lead and bismuth corrosion resistance of the coating are synergistically improved, and the coating is particularly suitable for structural material protection of a fourth-generation nuclear reactor coolant system.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a laser cladding coating with an in-situ self-generated TiC and Y-Ti-O composite reinforcing phase and its preparation method, belonging to the field of alloy protective coating technology. Background Technology

[0002] Liquid lead-bismuth eutectic alloy (LBE) is considered an ideal coolant for Generation IV nuclear reactors (such as lead-cooled fast reactors, LFR) and accelerator-driven subcritical systems (ADS) due to its excellent neutronics and thermophysical properties. However, the high-temperature flow of LBE can cause severe dissolution corrosion, oxidation corrosion, and cavitation corrosion to reactor structural materials (such as austenitic stainless steel), posing a significant threat to reactor safety and lifespan.

[0003] Preparing protective coatings on the surface of structural materials is currently the most direct and effective solution. Among them, Fe-Cr-Al series alloy coatings have attracted attention due to their ability to form a protective Al2O3 film on the surface. To further improve the mechanical properties and erosion resistance of the coating, hard phases such as TiC are often introduced for strengthening. However, directly added TiC is prone to segregation, resulting in weak bonding with the matrix and becoming a crack initiation point. Although in-situ self-generated TiC can improve interfacial bonding, its morphology and distribution are still difficult to control precisely, and it still has an adverse effect on the coating's toughness and crack resistance. Rare earth oxides (such as Y2O3) are often used as grain refiners to improve coating performance, but their mechanism of action is generally considered to be a physical dispersion distribution. In the existing technology, there is a lack of a technical solution that can simultaneously achieve the in-situ synthesis of multiple phases and form a stable composite reinforcing phase through chemical reaction, thereby comprehensively optimizing the coating's microstructure and properties. Summary of the Invention

[0004] The purpose of this invention is to overcome the shortcomings of the prior art and provide a laser cladding coating with an in-situ self-generated TiC and Y-Ti-O composite reinforcing phase and its preparation method, mainly solving the following technical problems: To address the problem of existing austenitic steels being susceptible to corrosion from liquid lead-bismuth eutectic alloys, a coating is provided that simultaneously resists heavy metal dissolution corrosion, oxidation corrosion, and liquid heavy metal erosion, thereby improving the safety and service life of reactor systems.

[0005] This addresses the problem in existing lead-bismuth corrosion-resistant coatings where the hard phase (such as TiC) exhibits poor morphology due to direct addition or in-situ formation, resulting in segregation, coarsening, and weak bonding with the matrix, thus becoming a crack initiation point and reducing the coating's bonding strength and toughness.

[0006] This addresses the problem that simply adding rare earth oxides (such as Y2O3) only works through physical dispersion, resulting in limited effects on microstructure refinement and performance improvement, and failing to effectively coordinate the relationship between the hard phase and the matrix phase.

[0007] This invention provides a composite coating (i.e., a laser cladding coating with an in-situ self-generated TiC and Y-Ti-O composite reinforcing phase) that can possess both excellent mechanical properties (high hardness, high bonding strength, and good wear resistance) and outstanding corrosion resistance (resistance to static corrosion and cavitation corrosion) in a high-temperature liquid lead-bismuth environment, thus exhibiting high oxidation resistance.

[0008] Meanwhile, the present invention provides a stable and controllable method for preparing the above-mentioned coating, which can effectively suppress defects such as cracks and pores during the laser cladding process.

[0009] Meanwhile, this invention provides an application of a laser cladding coating with an in-situ self-generated TiC and Y-Ti-O composite reinforcing phase.

[0010] To solve the above-mentioned technical problems, the technical solution adopted by the present invention is as follows: In a first aspect, the present invention provides a laser cladding coating having an in-situ self-generated TiC and Y-Ti-O composite reinforcing phase. The coating is clad onto the surface of a steel substrate, and its composition, by mass percentage, includes: Cr: 20-28%, Al: 18-22%, Ti: 18-22%, C: 2.5-3.2%, Y2O3: 0.1-1.0%, with the balance being Fe and unavoidable impurities.

[0011] The microstructure of the coating comprises an Fe2AlCr alloy matrix phase and an in-situ self-generated reinforcing phase dispersed within the matrix phase. The in-situ self-generated reinforcing phase comprises a TiC phase and a Y-Ti-O composite phase present within the TiC phase. The Y-Ti-O composite phase is preferably at least one of Y2Ti2O7 and Y2TiO5.

[0012] Preferably, the steel substrate is 304 or 316L austenitic stainless steel.

[0013] Preferably, the mass percentage of Y2O3 is 0.15%-0.25% (most preferably 0.2%). At this content, the TiC phase has an ellipsoidal or short rod-shaped morphology and is uniformly distributed within the grain boundaries and grains of the Fe2AlCr matrix phase, effectively avoiding segregation.

[0014] Preferably, the average Vickers hardness of the coating is not less than 440 HV, and the bonding strength between the coating and the steel substrate is not less than 280 MPa. Under optimal composition and process, the hardness can reach ~489 HV, and the bonding strength can reach ~435 MPa.

[0015] Secondly, the present invention provides a method for preparing the above-mentioned laser cladding coating, comprising the following steps: a. Ingredients: Weigh FeCrC alloy powder, FeAl alloy powder, pure Ti powder, and nano Y2O3 powder according to the composition ratio of the coating, and mix them by ball milling. Use three different sizes of grinding balls (Ø10 mm, Ø7 mm, Ø5 mm) with a mass ratio of 2:3:5. The ball-to-powder mass ratio is set to 1:1. During ball milling, add a small amount of sodium stearate powder (5g sodium stearate per 100mL of mixed powder) to avoid clumping and obtain a mixed powder. b. Drying the powder: Place the mixed powder in a vacuum drying oven and keep it at 120-200℃ for 60-120 minutes, then take it out and add it into the powder feeder; c. Protective Atmosphere: Fill the semi-enclosed chamber with an inert gas (such as argon, choosing an atmosphere with a density greater than air), introducing the gas from the bottom and filling for at least 5 minutes to ensure that all air inside the chamber is expelled. Maintain the inert gas venting at the bottom of the semi-enclosed chamber throughout the laser cladding process to ensure that the entire cladding process is conducted under an inert gas atmosphere. d. First Laser Cladding: Under a protective atmosphere, a coaxial powder feeding method is selected, and a laser beam is used for scanning and cladding. The laser incident direction forms a 75°~85° angle with the surface to be clad to avoid reflection damage to the equipment from components such as Al. The parameters for the first laser process are: laser power 2000-2200 W, scanning rate 5mm / s, and overlap rate 45%-55%. After completing a single-layer scan, the laser head returns to the initial position and powder feeding is paused. After waiting for approximately 30 seconds, the next cladding is performed.

[0016] e. Second laser cladding: After step d, a second laser cladding is performed. The laser incident direction forms a 75°~85° angle with the surface to be clad. The second scanning direction is perpendicular to the first scanning direction. The parameters for the second laser process are: laser power 2000-2400 W, scanning rate 4-6 mm / s, and overlap rate 30%-50%.

[0017] f. Post-treatment stress relief: The prepared samples were quickly transferred to a resistance furnace for stress-relief annealing. The annealing temperature was set at 500℃±10℃, the heating rate was 5℃ / min, and the holding time was 2h. After the holding time, the samples were cooled in the furnace until the furnace temperature dropped to 150℃ before being removed and air-cooled. This step aims to eliminate residual thermal stress generated during laser rapid solidification and prevent coating cracking. Simultaneously, the heat treatment process promotes the homogenization of the matrix composition and structure, stabilizes and improves the bonding interface between the in-situ generated nanoscale multiphase ceramic particles (such as Y2TiO5, Y2Ti2O7, and TiC) and the matrix, thereby fully utilizing their grain refinement and dispersion strengthening effects to improve the strength and toughness of the coating.

[0018] The present invention relates to the application of a laser cladding coating with an in-situ self-generated TiC and Y-Ti-O composite reinforcing phase in the protection of nuclear reactor structural components operating in a high-temperature liquid lead-bismuth eutectic alloy environment. The nuclear reactor structural components include a fourth-generation nuclear reactor coolant system.

[0019] Compared with the prior art, the present invention has the following significant advantages: 1. Synergistic Enhancement Effect: Through the in-situ reaction of Y₂O₃ and Ti, a composite phase of Y₂Ti₂O₇ and / or Y₂TiO₅ (i.e., Y-Ti-O phase) is formed within TiC while simultaneously generating TiC. The Y-Ti-O phase acts as the nucleation core of TiC, refining the TiC grains from coarse rod-shaped grains to fine ellipsoidal or short rod-shaped grains. This achieves multi-level composite strengthening through the inclusion of a third phase within a second phase, weakening the grain boundary wetting effect of the second phase (such as TiC) on the FeCrAl matrix phase, thereby significantly enhancing the strengthening effect.

[0020] 2. Overall performance improvement: Hardness and wear resistance: When the Y2O3 content is 0.2 wt.%, the coating hardness reaches its peak (~489 HV), which is much higher than that of the base steel (~205 HV). The coating exhibits excellent resistance to high-temperature oxidation wear, and its wear resistance is far superior to that of the 304 stainless steel substrate.

[0021] Bond strength: Compared to the coating without added Y2O3, the coating with 0.2 wt.% added Y2O3 has a bond strength that is increased by approximately 53.7% (~435 MPa).

[0022] Corrosion resistance: The coating can form a dense Al2O3 / Fe3O4 / TiO2 composite oxide layer in static LBE at 500℃, and the thickness after 1000 hours of corrosion is only about 0.4 μm, which is far superior to the substrate material. The addition of an appropriate amount of Y2O3 can also effectively inhibit intra-grain boundary oxidation and improve the resistance to cavitation corrosion.

[0023] 1. Controllable process and high coating quality: The laser cladding process parameter window provided by this invention can effectively suppress defects such as cracks and pores, and obtain a well-formed, dense coating that is firmly bonded to the substrate.

[0024] 2. Promising application prospects: This coating is specially designed to resist high-temperature LBE environments, providing a reliable technical solution for solving the corrosion problem of key structural materials in advanced nuclear energy systems.

[0025] This invention discloses a laser cladding coating with an in-situ self-generated TiC and Y-Ti-O composite reinforcing phase and its preparation method. The coating consists of Fe, Cr, Al, Ti, C, and Y2O3 in specific proportions and is prepared on a steel substrate using an optimized laser cladding process. Its core innovation lies in the fact that during laser processing, not only is a hard TiC phase synthesized in situ, but Y2O3 also reacts with Ti to generate Y2Ti2O7 and Y2TiO5, etc., Y-Ti-O composite phases, which exist as nucleation sites within the TiC particles. This unique "phase-within-a-phase" composite structure significantly refines and spheroidizes TiC, improving its distribution, thereby synergistically enhancing the coating's hardness, wear resistance, bonding strength with the substrate, and resistance to high-temperature liquid lead-bismuth corrosion. It is particularly suitable for structural material protection in fourth-generation nuclear reactor coolant systems. Attached Figure Description

[0026] Figure 1 SEM images of the coatings; where (a) 0 wt.% Y2O3; (b) 0.2 wt.% Y2O3; (c) 0.5 wt.% Y2O3; (d) 0.8 wt.% Y2O3; (e) 1.0 wt.% Y2O3; Figure 2 The images show the TEM results of the coatings; (a) 0 wt.% Y2O3 coating; (b) 0.2 wt.% Y2O3 coating; (c) TiC containing the Y-Ti-O composite phase in the 0.2 wt.% Y2O3 coating; (d) selected area electron diffraction pattern of region c; (e) and (f) high-resolution images of TiC particles containing Y2Ti2O7 and Y2TiO5. Figure 3 The coating hardness is represented by (a) the coating hardness distribution diagram and (b) the average hardness of the coating. Figure 4 To improve the Olla column method for testing coating hardness; wherein, (a) the bonding strength of the coating; (b) the bonding strength specimen; Figure 5 For static LBE corrosion tests; (a) 500 hours with 0.2 wt.% Y2O3 coating; (b) 500 hours with 304 stainless steel; (c) 1000 hours with 0.2 wt.% Y2O3 coating; (d) 1000 hours with 304 stainless steel. Figure 6 The cross-sectional morphology of each sample is shown after 5 hours of cavitation corrosion. Detailed Implementation

[0027] The present invention will now be described in further detail with reference to the accompanying drawings and specific embodiments. The following embodiments are for illustrative purposes only and are not intended to limit the scope of the invention.

[0028] While preferred embodiments of the invention are described below, it should be understood that the invention can be implemented in various forms and should not be limited to the embodiments set forth herein. Where specific techniques or conditions are not specified in the embodiments, they are performed in accordance with techniques or conditions described in the literature in the art or according to product instructions. Reagents or instruments whose manufacturers are not specified are all commercially available conventional products. The invention will now be described in detail with reference to specific embodiments. Example 1

[0029] Preparation of mixed powders: 1. Select the following raw material powders: FeCrC alloy powder: The composition is Cr 60 wt.%, C 7.5 wt.%, with the balance being Fe, and the particle size range is 45-105 μm.

[0030] FeAl alloy powder: composition is Al 50 wt.%, Fe 50 wt.%, particle size range is 45-105 μm.

[0031] Pure Ti powder: purity ≥ 99.999%, particle size range 45-105 μm.

[0032] Nano Y2O3 powder: purity ≥99.999%, particle size ≤50 nm.

[0033] 2. Weigh the powder according to the five components shown in Table 1 (unit: wt.%).

[0034] Table 1. Laser cladding powder composition design (unit: wt.%)

[0035] 3. Place the weighed powder into a planetary ball mill. Both the grinding jar and the grinding balls are made of 304 stainless steel. Use three different sizes of grinding balls (Ø10 mm, Ø7 mm, Ø5 mm) in a mass ratio of 2:3:5. The ball-to-powder mass ratio is set to 1:1. Add a small amount of sodium stearate powder during ball milling.

[0036] 4. After ball milling for 2 hours, sieve the powder and take the mixed powder with a particle size ≤45 μm for later use to ensure that the powder has good flowability and cladding performance.

[0037] Laser cladding for coating preparation: 1. Substrate Preparation: 304 austenitic stainless steel plate is selected as the substrate, with the following composition: C≤0.08%, Mn≤2.00%, Si≤1.00%, Cr: 18.0-20.0%, Ni: 8.0-11.0%, P≤0.045%, S≤0.030%, and the balance being Fe. The steel plate is wire-cut into 100 mm × 50 mm × 10 mm dimensions, and the surface is cleaned with alcohol to remove oil stains.

[0038] 2. Powder Pre-treatment: The prepared mixed powder was placed in a vacuum drying oven at 200°C for 2 hours to remove moisture. Then, the powder was evenly spread on the surface of a stainless steel substrate using a mold, controlling the pre-treatment layer thickness to be 0.5 mm. The powder was then compacted using a fully automatic powder tablet press at a pressure of 20 GPa for 5 minutes to form a dense pre-treatment layer.

[0039] 3. First laser cladding: The substrate is fixed on the laser robot's worktable. Argon gas with a purity of 99.99% is introduced as a protective gas to prevent oxidation of the molten pool. The process parameters are set as follows: laser incident direction at an 80° angle to the surface to be fused, laser power 2200 W, scanning rate 5 mm / s, and overlap rate 50%. The robotic arm is controlled to scan along the set path.

[0040] 4. Second Laser Cladding: After the above steps are completed, a second laser cladding is performed. The laser incident direction forms an 80° angle with the surface to be clad. The second scanning direction is perpendicular to the first scanning direction. The parameters for the second laser process are: laser power 2400 W, scanning rate 4 mm / s, and overlap rate 40%.

[0041] 5. Post-treatment for stress relief: Quickly transfer the prepared sample from the above steps to a resistance furnace for stress-relief annealing. The annealing temperature is set at 500℃, the heating rate is 5℃ / min, and the holding time is 2 hours. After the holding time, use furnace cooling. Once the furnace temperature drops to 150℃, open the furnace and remove the sample for air cooling.

[0042] Coating microstructure and property characterization: 1. Microstructure analysis: like Figure 1 As shown, scanning electron microscopy (SEM) was used to observe the metallographic structure of coatings with different Y₂O₃ contents. Without Y₂O₃, TiC appeared as coarse rods, mainly agglomerated at grain boundaries. After adding 0.2 wt.% Y₂O₃, TiC became fine ellipsoids or short rods, uniformly distributed within the grains and at grain boundaries. When the Y₂O₃ content increased to 0.8 wt.% or higher, TiC again showed significant grain boundary agglomeration.

[0043] Transmission electron microscopy (TEM): Detailed analysis of the 0.2 wt.% Y₂O₃ coating was performed. TEM analysis further confirmed that Y₂Ti₂O₇ and Y₂TiO₅ nanoparticles were encapsulated within ellipsoidal TiC particles with a size of 300-600 nm (see...). Figure 2 This indicates that the Y-Ti-O phase, acting as nucleation sites, promotes the nucleation of TiC, resulting in more in-situ generated TiC appearing inside the grains. This alters the morphology and distribution of TiC, weakens the grain boundary wetting effect of the second phase, such as TiC, on the FeCrAl matrix phase, and thus significantly improves the coating's hardness, wear resistance, and resistance to lead-bismuth corrosion.

[0044] 2. Mechanical property testing: Hardness: The hardness of the coating cross-section was tested using a microhardness tester. Results are as follows: Figure 3 The results showed that the coating with 0.2 wt.% Y2O3 added had the highest average hardness, approximately 489 HV. The coatings without added Y2O3 and with other Y2O3 contents had hardnesses between 440 and 450 HV, all significantly higher than the 205 HV of the 304 stainless steel substrate.

[0045] Bond strength: Tested using the modified Olla column method. Figure 4 As shown, the coating with 0.2 wt.% Y2O3 added had the highest bonding strength, reaching 435 MPa, which was about 53.7% higher than the coating without added Y2O3 (283 MPa). As the Y2O3 content continued to increase, the bonding strength gradually decreased, but it was still higher than the coating without added Y2O3.

[0046] Wear resistance: Pin-disc friction and wear test was conducted at 400℃. The coating without added Y2O3 showed the best wear resistance, but as the amount of added Y2O3 increased, the wear resistance decreased due to the increase in hard abrasive particles. However, all coatings were far superior to 304 stainless steel.

[0047] 3. Corrosion resistance test: Static LBE corrosion: such as Figure 5 As shown, the coated samples were etched in a static LBE at 500℃ and oxygen saturation for 1000 hours. A dense Al2O3 / Fe3O4 / TiO2 mixed oxide layer was formed on all coated surfaces, with a thickness of only about 0.4 μm, which is much lower than the ~10.5 μm of 304 stainless steel.

[0048] LBE cavitation corrosion: Cavitation corrosion is achieved by using an ultrasonic generator to create cavitation bubbles in a liquid lead-bismuth eutectic alloy (LBE) that impact the sample surface, simulating the corrosive effects of flowing liquid on the sample surface, such as erosion and bubble collapse. Therefore, the sample surface is simultaneously subjected to dissolution corrosion, oxidation corrosion, and cavitation corrosion by the liquid heavy metal. Cavitation corrosion tests were conducted in LBE at 500℃. Figure 6As shown, the coating with 0.2 wt.% Y2O3 exhibited the best performance, with the shallowest surface cavitation pits (maximum depth of only 4.694 μm after 5 hours), because it effectively suppressed the internal oxidation of Al elements along grain boundaries. Excessive Y2O3 (such as 1.0 wt.%) caused severe segregation of TiC, which easily led to large-area oxidation corrosion, resulting in rapid peeling of the coating and performance even lower than that of the substrate.

[0049] Overall effect analysis: The core technical effects of this invention are fully demonstrated through a comparison between (0.2 wt.% Y2O3) and a comparative example (304 austenitic stainless steel, no Y2O3 added, and a poorly processed coating): Under optimal composition (0.2 wt.% Y2O3) and optimal process, in-situ symbiosis of TiC and Y-Ti-O phases was successfully achieved, resulting in a coating with uniform microstructure, no macroscopic cracks, high hardness, excellent bonding strength, and excellent resistance to LBE corrosion (especially cavitation corrosion).

[0050] Deviations from optimal processes or compositions, such as insufficient Y2O3 (0 wt.%), will prevent the formation of the Y-Ti-O phase and the refinement of TiC; excessive Y2O3 (≥0.8 wt.%) will lead to TiC segregation and performance degradation; improper laser processes will introduce defects such as cracks.

[0051] This embodiment describes the application of a laser cladding coating with an in-situ self-generated TiC and Y-Ti-O composite reinforcing phase in the protection of nuclear reactor structural components operating in a high-temperature liquid lead-bismuth eutectic alloy environment. The nuclear reactor structural components include a fourth-generation nuclear reactor coolant system.

[0052] Example 2

[0053] A laser cladding coating with an in-situ self-generated TiC and Y-Ti-O composite reinforcing phase is clad onto the surface of 316L austenitic stainless steel. The coating comprises an Fe2AlCr alloy matrix phase and an in-situ self-generated reinforcing phase dispersed within the Fe2AlCr alloy matrix phase. The in-situ self-generated reinforcing phase includes a TiC phase and a Y-Ti-O composite phase present within the TiC phase. The TiC phase consists of ellipsoidal TiC particles with a size of 300-600 nm, distributed at grain boundaries and within grains of the Fe2AlCr alloy matrix phase. The coating composition by mass percentage includes: Cr: 20%, Al: 18%, Ti: 18%, C: 2.5%, Y2O3: 0.2%, with the balance being Fe and unavoidable impurities.

[0054] A method for preparing a laser cladding coating with an in-situ self-generated TiC and Y-Ti-O composite reinforcing phase includes the following steps: a. Ingredients: Weigh out FeCrC alloy powder, FeAl alloy powder, pure Ti powder and nano Y2O3 powder according to the composition ratio of the coating, and mix them by ball milling. Use three different sizes of grinding balls: Ø10 mm, Ø7 mm and Ø5 mm, with a mass ratio of 2:3:5 and a ball-to-powder mass ratio of 1:1. Add a small amount of sodium stearate powder during ball milling to prevent agglomeration and obtain a mixed powder. b. Drying the powder: Vacuum dry the mixed powder, keep it at 120°C for 60 minutes, then take it out and add it into the powder feeder; c. Protective atmosphere: Inert argon gas is filled into the semi-enclosed box. The inert gas is introduced from the bottom of the semi-enclosed box and filled for at least 5 minutes to ensure that the air inside the box is exhausted. During the laser cladding process, the bottom of the semi-enclosed box is kept in an inert gas venting state to ensure that the cladding process is carried out in an inert gas atmosphere. d. First laser cladding: Under a protective atmosphere, a coaxial powder feeding method is selected, and a laser beam is used for scanning cladding; the laser incident direction is at a 75° angle to the surface to be clad. The first laser process parameters are: laser power 2000 W, scanning rate 5 mm / s, and overlap rate 45%; after completing a single-layer scan, the laser head returns to the initial position and powder feeding is paused, and after waiting for 30 seconds, the next cladding is performed. e. Second laser cladding: After step d, a second laser cladding is performed; the laser incident direction is at a 75° angle to the surface to be clad, the second scanning direction is perpendicular to the first scanning direction, and the second laser process parameters are: laser power 2000W, scanning rate 6 mm / s, and overlap rate 30%; f. Post-treatment stress relief: The above samples were transferred to a resistance furnace for stress relief annealing. The annealing temperature was 490℃, the heating rate was 5℃ / min, and the holding time was 2h. After the holding time, the samples were cooled in the furnace until the furnace temperature dropped to 150℃ before being taken out and air-cooled.

[0055] This embodiment describes the application of a laser cladding coating with an in-situ self-generated TiC and Y-Ti-O composite reinforcing phase in the protection of nuclear reactor structural components operating in a high-temperature liquid lead-bismuth eutectic alloy environment. The nuclear reactor structural components include a fourth-generation nuclear reactor coolant system.

[0056] Example 3

[0057] A laser cladding coating with an in-situ self-generated TiC and Y-Ti-O composite reinforcing phase is clad onto the surface of 316L austenitic stainless steel. The coating comprises an Fe2AlCr alloy matrix phase and an in-situ self-generated reinforcing phase dispersed within the Fe2AlCr alloy matrix phase. The in-situ self-generated reinforcing phase includes a TiC phase and a Y-Ti-O composite phase present within the TiC phase. The TiC phase consists of ellipsoidal TiC particles with a size of 300-600 nm, distributed at grain boundaries and within grains of the Fe2AlCr alloy matrix phase. The coating composition by mass percentage includes: Cr: 28%, Al: 22%, Ti: 22%, C: 3.2%, Y2O3: 0.2%, with the balance being Fe and unavoidable impurities.

[0058] A method for preparing a laser cladding coating with an in-situ self-generated TiC and Y-Ti-O composite reinforcing phase includes the following steps: a. Ingredients: Weigh out FeCrC alloy powder, FeAl alloy powder, pure Ti powder and nano Y2O3 powder according to the composition ratio of the coating, and mix them by ball milling. Use three different sizes of grinding balls: Ø10 mm, Ø7 mm and Ø5 mm, with a mass ratio of 2:3:5 and a ball-to-powder mass ratio of 1:1. Add a small amount of sodium stearate powder during ball milling to prevent agglomeration and obtain a mixed powder. b. Drying the powder: Vacuum dry the mixed powder, keep it at 120°C for 60 minutes, then take it out and add it into the powder feeder; c. Protective atmosphere: Inert argon gas is filled into the semi-enclosed box. The inert gas is introduced from the bottom of the semi-enclosed box and filled for at least 5 minutes to ensure that the air inside the box is exhausted. During the laser cladding process, the bottom of the semi-enclosed box is kept in an inert gas venting state to ensure that the cladding process is carried out in an inert gas atmosphere. d. First laser cladding: Under a protective atmosphere, a coaxial powder feeding method is selected, and a laser beam is used for scanning cladding; the laser incident direction is at an 85° angle to the surface to be clad. The first laser process parameters are: laser power 2000 W, scanning rate 5 mm / s, and overlap rate 55%; after completing a single-layer scan, the laser head returns to the initial position and powder feeding is paused, and after waiting for 30 seconds, the next cladding is performed. e. Second laser cladding: After step d, a second laser cladding is performed; the laser incident direction is at an 85° angle to the surface to be clad, the second scanning direction is perpendicular to the first scanning direction, and the second laser process parameters are: laser power 2200W, scanning rate 5 mm / s, and overlap rate 50%; f. Post-treatment stress relief: The above samples were transferred to a resistance furnace for stress relief annealing. The annealing temperature was 510℃, the heating rate was 5℃ / min, and the holding time was 2h. After the holding time, the samples were cooled in the furnace until the furnace temperature dropped to 150℃ before being taken out and air-cooled.

[0059] This embodiment describes the application of a laser cladding coating with an in-situ self-generated TiC and Y-Ti-O composite reinforcing phase in the protection of nuclear reactor structural components operating in a high-temperature liquid lead-bismuth eutectic alloy environment. The nuclear reactor structural components include a fourth-generation nuclear reactor coolant system.

[0060] It should be understood that, in order to simplify this disclosure and aid in understanding one or more of the various aspects of the invention, features of the invention are sometimes grouped together in a single embodiment, figure, or description thereof in the above description of exemplary embodiments of the invention. However, this method of disclosure should not be interpreted as reflecting an intention that the claimed invention requires more features than expressly recited in each claim. Rather, as reflected in the claims, inventive aspects lie in fewer than all the features of the foregoingly disclosed embodiments. Therefore, the claims, following the detailed description, are hereby expressly incorporated into that detailed description, wherein each claim itself is a separate embodiment of the invention.

[0061] Although the invention has been described with reference to a limited number of embodiments, those skilled in the art will understand from the foregoing description that other embodiments are conceivable within the scope of the invention described herein. Furthermore, it should be noted that the language used in this specification has been chosen primarily for readability and instructional purposes, and not for the purpose of interpreting or limiting the subject matter of the invention. Therefore, many modifications and variations will be apparent to those skilled in the art without departing from the scope and spirit of the appended claims. The disclosure of the invention is illustrative and not restrictive, and the scope of the invention is defined by the appended claims.

[0062] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A laser cladding coating having an in-situ self-generated TiC and Y-Ti-O composite reinforcing phase, characterized in that, The coating is fused onto the surface of the steel substrate; The coating comprises an Fe2AlCr alloy matrix phase and an in-situ self-generated reinforcing phase dispersed in the Fe2AlCr alloy matrix phase; The in-situ self-generated reinforced phases include the TiC phase and the Y-Ti-O composite phase existing inside the TiC phase.

2. The laser cladding coating with an in-situ self-generated TiC and Y-Ti-O composite reinforcing phase according to claim 1, characterized in that, Coating composition by mass percentage Includes: Cr: 20-28%, Al: 18-22%, Ti: 18-22%, C: 2.5-3.2%, Y2O3: 0.1-1.0%, with the balance being Fe and unavoidable impurities.

3. The laser cladding coating with an in-situ self-generated TiC and Y-Ti-O composite reinforcing phase according to claim 2, characterized in that, The mass percentage of Y2O3 is 0.15%-0.25% or 0.2% by mass.

4. The laser cladding coating with an in-situ self-generated TiC and Y-Ti-O composite reinforcing phase according to claim 1, characterized in that, The TiC phase consists of ellipsoidal TiC particles with a size of 300-600 nm; the TiC phase is distributed in the grain boundaries and grain interiors of the Fe2AlCr alloy matrix phase; the Y-Ti-O composite phase includes at least one of Y2Ti2O7 and Y2TiO5.

5. The laser cladding coating with an in-situ self-generated TiC and Y-Ti-O composite reinforcing phase according to claim 1, characterized in that, The average Vickers hardness of the coating is not less than 440 HV, and the bonding strength between the coating and the steel substrate is not less than 280 MPa; under optimal composition and process, the average Vickers hardness of the coating reaches 489 HV, and the bonding strength between the coating and the steel substrate reaches 435 MPa.

6. The laser cladding coating with an in-situ self-generated TiC and Y-Ti-O composite reinforcing phase according to claim 1, characterized in that, The steel base is 304 or 316L austenitic stainless steel.

7. A method for preparing a laser cladding coating with an in-situ self-generated TiC and Y-Ti-O composite reinforcing phase according to any one of claims 1 to 6, characterized in that, Includes the following steps: a. Ingredients: Weigh out FeCrC alloy powder, FeAl alloy powder, pure Ti powder, and nano Y2O3 powder according to the composition ratio of the coating, and mix them by ball milling. Use three different sizes of grinding balls: Ø10 mm, Ø7 mm, and Ø5 mm, with a mass ratio of 2:3:5 and a ball-to-powder mass ratio of 1:

1. Add sodium stearate powder during ball milling to prevent agglomeration and obtain a mixed powder. b. Drying the powder: Dry the mixed powder, then remove it and add it into the powder feeder; c. Protective atmosphere: Inert gas is filled into the semi-enclosed box. The inert gas is introduced from the bottom of the semi-enclosed box and filled for at least 5 minutes to ensure that the air inside the box is exhausted. During the laser cladding process, the inert gas at the bottom of the semi-enclosed box is kept in a ventilated state to ensure that the cladding process is carried out in an inert gas atmosphere. d. First laser cladding: Under a protective atmosphere, a coaxial powder feeding method is selected, and a laser beam is used for scanning cladding; the laser incident direction is at an angle of 75°~85° to the surface to be clad. The first laser process parameters are: laser power 2000-2200 W, scanning rate 5 mm / s, and overlap rate 45%-55%; after completing a single-layer scan, the laser head returns to the initial position and powder feeding is paused, waiting for 30 seconds before the next cladding is performed; e. Second laser cladding: After step d, a second laser cladding is performed; the laser incident direction is at an angle of 75°~85° to the surface to be clad, the second scanning direction is perpendicular to the first scanning direction, and the second laser process parameters are: laser power 2000-2400 W, scanning rate 4-6 mm / s, overlap rate 30%-50%; f. Post-treatment stress relief: The above samples are transferred to an electric resistance furnace for stress relief annealing.

8. The preparation method according to claim 7, characterized in that, In step c, the inert gas includes argon.

9. The preparation method according to claim 7, characterized in that, In step f, the annealing temperature is 500℃±10℃, the heating rate is 5℃ / min, and the holding time is 2h. After the holding time is completed, the furnace is cooled in tandem with the furnace. After the furnace temperature drops to 150℃, the furnace is opened and the furnace is removed for air cooling.

10. The application of a laser cladding coating with an in-situ self-generated TiC and Y-Ti-O composite reinforcing phase, as described in any one of claims 1 to 6, in the protection of nuclear reactor structural components operating in a high-temperature liquid lead-bismuth eutectic alloy environment, characterized in that... Nuclear reactor structural components include the fourth-generation nuclear reactor coolant system.